Non-alcoholic fatty liver disease is associated with an increased mortality in adult patients with group B Streptococcus invasive disease : Nealkoholna masna bolest jetre povezana je s većom smrtnošću kod odraslih bolesnika s invazivnom bolešću uzrokovanom streptokokom grupe B - Gjurašin, Branimir, liječnik (Array, 2021)
Background: Group B Streptococcus (GBS) is a significant cause of invasive disease among adult non-pregnant patients with increasing incidence and mortality rates. Although non-alcoholic fatty liver disease (NAFLD) is associated with components of metabolic syndrome previously recognized as risk factors for GBS, the impact of NAFLD on GBS course and outcomes is unknown. Methods: We conducted a retrospective cohort study of all non-pregnant adult patients diagnosed with invasive GBS infection during a 15-year period. Results: 102 patients were included in the study (46.1% males; median age 69, IQR 58-78 years). Disease primarily presented as bacteremia without a defined source (37; 36.3%), cellulitis/erysipelas (35; 34.3%), pneumonia (13; 12.7%) and endocarditis (8; 7.8%). The most common comorbidities were diabetes (42; 41.2%), dyslipidemia (39; 38.2%), cardiovascular disease (34; 33.3%), peripheral vascular disease (21; 20.6%), obesity (21; 20.6%) and malignancy (10; 9.8%). Based upon the results of abdominal ultrasound, the patients were divided into two groups: the ones with steatosis (44; 43.1%) and the ones without steatosis (58; 56.9%). There were no significant differences in clinical presentations and comorbidities between groups. In-hospital mortality was 29.5% (13/44) in patients with NAFLD and 10.3% (6/58) in the control group (p=0.0200). Endocarditis (OR 6.69; 95%CI 1.045-44.46, p=0.0410), acute renal failure (OR 13.92; 95%CI 3.00-77.71, p=0.0013), qSOFA >2 (OR 23.93; 95%CI 4.66-171.2) and NAFLD (OR 6.64; 95%CI 1.23-47.88, p=0.0258) were independently associated with in-hospital mortality. Conclusions: NAFLD is associated with higher mortality in patients suffering from invasive GBS disease which appears to be independent of other components of the metabolic syndrome, such as obesity and diabetes mellitus.